Anaphora, Possible Worlds, and Temporal Schemas: Locating the Future in Public and Religious Discourses (ENTHYMEMA, 2013)
Cognitive poetics has often investigated only literary reading practices. This article examines how one particular method of cognitive poetics, text world theory, can be used to understand the cognitive reading practices based upon Christian hermeneutic systems of temporality. To differentiate religious rhetoric from persuasive public rhetoric, the article examines text and discourse worlds in 1980s British Labour Party rhetoric, in the rhetoric of the Sermon on the Mount, and in Catholic social activist rhetoric.
Keywords: Cognitive poetics; text world theory; religious discourse; public rhetoric